2020
DOI: 10.1002/osp4.387
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, but not overweight, is associated with plantar light touch sensation in children aged 8 to 16 years: A cross‐sectional study

Abstract: Summary Objective Increased foot‐ground contact loading engenders adaptive glabrous skin thickening and can decrease mechanoreceptor acuity and alter plantar cutaneous sensation. There has not been any research on whether overweight and obesity are similarly associated with normal plantar cutaneous sensation scores in children. This study investigated the associations between normal plantar cutaneous sensation scores and weight status (i.e., healthy weight, overweight, and obesity) in a sample of youth. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…(2015) showed that skin hardness was positively correlated not only with perceptual threshold but also with afferent firing by fast adapting foot sole mechanoreceptors. These findings support the Ajisafe et al. (2020) hypothesis.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…(2015) showed that skin hardness was positively correlated not only with perceptual threshold but also with afferent firing by fast adapting foot sole mechanoreceptors. These findings support the Ajisafe et al. (2020) hypothesis.…”
Section: Discussionsupporting
confidence: 87%
“…Our study revealed a detailed map of cutaneous foot sole sensibility decay in the participant group with morbid obesity that warrants further explanation. In an attempt to explain the low foot sole sensibility of individuals with obesity, Ajisafe et al. (2020) suggested that obesity and associated mechanical stress to support heavier body weight in daily living tasks lead to adaptive glabrous skin thickening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations